2002
DOI: 10.1007/s702-002-8238-9
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA of the NR1 subtype of glutamate receptor in Alzheimer's disease

Abstract: Glutamate has been implicated in the pathogenesis of Alzheimer's disease (AD). Controversial data exists regarding changes in the N-methyl-D-aspartate (NMDA) receptor complex in AD. We wished to elucidate the hypothesis that the NMDA receptor system is involved in the pathogenesis of AD using a gene expression approach targeting the mRNA of the universal subtype of the NMDA receptor NR1. This was performed using in situ hybridization and antisense 35S-labelled oligonucleotides on brain tissue collected at post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…These reductions were also associated with reductions of NR2A and NR2B in entorhinal cortex but not in the occipital cortex or caudate in the same study. Other groups confirmed that there was a trend towards a reduction in NR1 mRNA in the hippocampus in AD by in situ hybridization [59]. Ligand binding and autoradiographic techniques have also generated controversial data.…”
Section: Nmda Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions were also associated with reductions of NR2A and NR2B in entorhinal cortex but not in the occipital cortex or caudate in the same study. Other groups confirmed that there was a trend towards a reduction in NR1 mRNA in the hippocampus in AD by in situ hybridization [59]. Ligand binding and autoradiographic techniques have also generated controversial data.…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…While the expression level and localization of NMDA receptors have been extensively studied in AD, the regulation of NMDA receptor expression is still controversial. Ikonomovic et al [55] reported that the NMDA GluR subunit NR1 is markedly increased in vulnerable neurons of AD, while other reports indicated that there was a reduction of NMDA receptors in AD [56][57][58], or no difference between AD and age-matched controls [59][60][61][62] (summarized in table 1). Results of immunoblot analyses show the level of NR1 is not altered in the dentate gyrus region of hippocampus [61].…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…79 However, most reports suggest that there is a decrease in protein and mRNA levels of these receptors, at least in later stages of the disease. 62,63,80,81 Discrepancies in these results could be explained by differences in the severity of the disease, as there is evidence of increased synaptic activity in individuals with mild cognitive impairment. 62,81 Autoradiography studies have shown reduced NMDA receptor binding in the CA1 and CA3 regions of the hippocampus, supporting the idea that there are fewer NMDA receptors in these areas of the brain.…”
mentioning
confidence: 99%
“…It has been reported that NMDA receptors are decreased in the cortical regions and hippocampus in AD brains [39] . A reduction in NMDA receptor subunit 1 mRNA in the hippocampus and an increase in the frontal and temporal cortices have also been observed [40] . In in vitro studies, the addition of Aβ enhances glutamate release from primary cultured microglia of rats [15] and increases the toxicity of glutamate [41] .…”
Section: N-methyl-d-aspartate Receptors In Admentioning
confidence: 94%